Segment Reduction-Based SVPWM Applied Three-Level F-Type Inverter for Power Quality Conditioning in an EV Proliferated Distributed System - Meenakshi Madhavan; Chellammal N.; Ramesh C. Bansal (International Transactions on Electrical Energy Systems)
The objective of this paper lies in the realization of a three-level F-type inverter (3L-FTI) as a shunt active filter in an EV-proliferated environment. The switches are triggered using segment reduced space vector pulse width modulation (SVPWM). This modulation technique provides a lower number of switching transitions than existing PWM strategies. Consequently, the inverter switches experience a decrease in both switching stress and switching losses. A 3L-FTI is a diode-free structure that reduces the harmonics in the source current with a high power factor (PF), where instantaneous reactive power (IRPT) theory is employed to generate the reference currents from the utility grid. In contrast to traditional three-level inverters, two-thirds of switches in 3L-FTI can tolerate a voltage stress equal to half of the DC input voltage. While studying the behaviour of this shunt active filter, with three different nonlinear loading conditions, the current total harmonic distortion (THD) is reduced from 28.43% to 2.13% after compensation, which is under 5% of IEEE standard 519-2014. Therefore, the 3L-FTI controlled by segment reduction SVPWM can be considered as better candidate for active filter in an EV proliferated distribution system.